Work together anywhere : a handbook on working remotely successfully for individuals, teams & managers - Sutherland, Lisette; Janene-Nelson, K.; Appelo, Jurgen, 1969- (Hoboken, New Jersey Wiley, 2020)
"In today's modern global economy, companies and organizations in all sectors are embracing the game-changing benefits of the remote workplace. Managers benefit by saving money and resources and by having access to talent outside of their zip codes, while employees enjoy greater job opportunities, productivity, independence, and work-life satisfaction. But in this new digital arena, companies need a plan for supporting efficiency and fostering streamlined, engaging teamwork. Packed with hands-on materials and actionable advice for cultivating agility, camaraderie, and collaboration, Work Together Anywhere is a thorough and inspiring must-have guide for getting ahead in today's remote-working world."--
How to use this book -- Foreword by Jurgen Appelo -- Introduction -- Part I: setting the scene: some of the who, what, where, and why of remote working -- Why are individuals going remote? -- How remote working benefits employers -- Frequently asked questions -- At a glance: how to replicate online the benefits of working on-site -- Part II: individuals working remotely -- Remote working 101: getting started -- Remote working 201: perfecting your game -- Questionnaire for individuals: are you ready to work remotely? -- Convincing your boss -- Seeking remote employment -- FlexJobs list -- Part III: successful remote teams 101: transitioning and hiring -- Transitioning toward the remote option -- Hiring remote workers and teams -- Hiring cheat sheet: what to look for when interviewing remote workers -- Remote-only manifesto -- Part IV: successful remote teams 201: managing remote workers and teams -- Commit and lead, trust and succeed -- Facilitate their success with leadership, alignment, and a full arsenal -- Tune your team with a team agreement -- Bring it all together -- Manager's action plan -- Remote team agreement -- Tips for online meetings: Facilitators -- Tips for online meetings: Participants -- Conclusion: doing great things together -- Acknowledgments & early adopters -- Resources -- About the authors.
Includes bibliographical references and index.
110251
Keywords: Telecommuting; Flexible work arrangements; Organizational effectiveness; Business & Economics -- Business Communication; Business & Economics -- Management; Business & Economics -- Personal Success; Flexible work arrangements; Organizational effectiveness; Telecommuting